Trauma und Terror Zum palästinensischen und tschetschenischen Nationalismus - Szyszkowitz, Tessa (2007)
Although small and not particularly peoples both Chechens and Palestinians became famous for suicide bomber attacks in recent years. This can - partly - be explained by the unrecognised collective traumas of the past. Both Chechens and Palestinians experienced collective traumas in the 1940ties. The entire Chechen population wad deported by Josef Stalin to Kasakhstan, Kirgysia and Sibiria in February 1944 under the pretext of collaboration with the Third Reich. Those who survived were allowed to return in 1957 to Chechenya. Half of the Palestinian Arab population was expelled from Palestine in 1947/48, when fighting erupted between Jews and Arabs. The refugees were never allowed to return. The memory of the deportation/expulsion was kept alive. The founding traumas contributed to the development of Chechen and Palestinian nationalism. Chechens and Palestinians till today suffer from their collective traumas, which stayed unrecognised and therefore create psychological and political problems for the following generations - and for their adverseries. The phenomenon of the "closed circle of violence" created a phobic collective behaviour, which led for example Chechens to the illusionary declaration of independence in 1991. It also led to the individual overreaction of young Chechens or Palestinians, who became living bombs. The collective Trauma, if untreated, poses a threat to any peaceful political solution.